T2 mapping in the quantitative evaluation of articular cartilage changes in children with hemophilia: A pilot study. Issue 4 (8th January 2019) - Zhang, Ningning; Lv, Yanqiu; Liu, Yue; Yin, Guangheng; Hu, Di; Wu, Runhui; Peng, Yun
ABSTRACT: Importance: Joint disease affects more than 90% of severe hemophiliacs. Early diagnosis is critical in preventing hemophilic arthritis. Magnetic resonance imaging (MRI) enables visualization of early arthropathic changes and plays an important role in treatment. Objective: To evaluate the role of T2 mapping in detecting early cartilage lesions in the knee and ankle joints of children with hemophilic arthropathy. Methods: Target joints of 15 male patients with clinically confirmed moderate or severe hemophilia were evaluated with MRI. In addition to routine MRI protocols (T1WI, T2_FFE, T2_SPAIR, PDW_TSE), T2 mapping was used to evaluate the articular cartilage of target joints. Results: The mean T2 value of the distal femoral cartilage was 46.72 ± 10.94 ms, which is higher than the reported age‐matched normal value (40.27 ± 3.50 ms). The mean T2 value of the proximal tibial cartilage was 45.60 ± 8.82 ms, which is higher than the reported normal value (31.15 ± 1.86 ms). Four examined joints (two ankles, two knees) showed normal morphology with no abnormal signal on routine MR sequences. However, T2 mapping showed locally increased T2 values in the cartilage, along with uneven color scales. Interpretation: The quantitative assessment method of T2 mapping might be helpful to early diagnosis for articular cartilage lesions. It might be a potential tool for early assessment of cartilage changes and quantification of lesion's severity for hemophilia joint.